Synchronization and tracking control of a novel 3 dimensional chaotic system - Jasim, Basil H.; Rashid, Mofeed Turky; Omran, Khulood Moosa (Iraqi Journal for Electrical and Electronic Engineering, 2020)
In this article, a novel three dimensional chaotic systems is presented. An extensive analysis including Lyapunov exponents, dissipation, symmetry, rest points with their properties is introduced. An adaptive tracking control system for the proposed chaos system has been designed. Also, synchronization system for two identical systems has been designed. The simulation results showed the effectiveness of the designed tracking and synchronization control systems.